DETERMINANTS OF CORPORATE SOCIAL RESPONSIBILITY (CSR) COST - Widyasti, safira Anggra; Saputro, Julianto Agung (Jurnal Perilaku dan Strategi Bisnis, 2023)
This research aim conducted to provide empirical evidence regarding the determinants that affect the cost of CSR. The variables X used are profitability (ROA), firm size, tax avoidance (ETR), and using CSR costs as the variable Y. This research takes data using a purposive sampling method on banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The analytical method used is multiple regression analysis and using Eviews 12 software, with a significance level of 0.05 (Î±=5%) and 0,1 (Î±=10%). the results of the study show that firm size and tax avoidance had a positive effect and significant effect on CSR costs. However, ROA had no effect and significant effect on CSR costs. This research also shows that the independent variable had able to predict the dependent variable reliably.